“And time future contained in time past”: British Modernist Poetry from T.S. Eliot to Ted Hughes - Tatiana N. Krasavchenko (Studia Litterarum)
It seems that T.S. Eliot (1888–1965) and Ted Hughes (1930–1998) are poets of different individual talents and epochs. Hughes, a poet of the second half of the 20 th century, concentrated on the conflict between Nature and the human being destroying Nature and thus preparing the end of the humanity. T.S. Eliot was a poet of urban civilization, a reformer of the Anglophone modernist poetry. In his days, the “poetry of Nature” rooted in the pastoral poetry of the 17 th –18 th centuries and in Romanticism, existed but only at the margins of mainstream poetic trends. Nevertheless, one can find it even in Eliot’s poetry, particularly in his Landscapes — poems written at the beginning of the 1930s. Also, both Eliot and Hughes were modernists. Eliot standing at the beginning of modernism, Hughes at its end; though the latter lived in the time of postmodernism, he was not a postmodernist himself since he was not engaged in the deconstruction and fragmentation of the “world model.” Like Eliot, he was a poet with integral Weltanschauung and a bright individual talent. Like Eliot, he was a traditionalist, though Eliot being an American was a “conscious traditionalist,” while Hughes, an Englishman, was most likely a “born” traditionalist: instead of deconstructing tradition, he was bearing on it. His “great tradition” included Shakespeare, Blake, Coleridge, Kipling, Graves, and Dylan Thomas. Both Eliot and Hughes are poets of eschatological trend and mythologists. However, one will not find Eliot among the authorities enlisted by Hughes in his “great tradition.” In the time of Hughes, Eliot was rejected due to the regular change of mainstreams trends. British poetry in the second half of the 20 th century is “tired” of urban poetry, of “Nature denial,” so it comes back to its track, and the motives that existed in Eliot’s poetry only in the background are now brought to the forefront.